Peran Orangtua dalam Pendidkan Calon Imam sebelum Memasuki Jenjang Pendidikan Seminari Menengah - Roberto Reno Sitepu (Litbang STFT Widya Sasana Malang, 2019)
The first and the most important education for seminarians happens in their family. Unfortunately, there are some parents who don’t realize their significant role on their children education because they let they children to have their education on school and Church. Parents can give support as well as obstacles for their children who want to continue their education in seminary. Parents shape the basic personal character and religios life for their children, while seminary only improve their consiciousness of their identity as candidate of priest which has emerged since their life in their family. That is the reason why parents must realize and maximize their important role to recognize the character of their children, to provide understanding and motivation, and to prepare their children before enter seminary.